2023
DOI: 10.1021/acsaelm.2c01428
|View full text |Cite
|
Sign up to set email alerts
|

Interface-Assisted Room-Temperature Magnetoresistance in Cu-Phenalenyl-Based Magnetic Tunnel Junctions

Abstract: Delocalized carbon-based radical species with unpaired spin, such as the phenalenyl (PLY) radical, have opened avenues for developing multifunctional organic spintronic devices. Using direct laser writing and in situ deposition, we successfully fabricated Cu-PLY-and Zn-PLY-based organic magnetic tunnel junctions (OMTJs) with improved morphology and a reduced junction area of 3 × 8 μm 2 . The nonlinear and weakly temperature-dependent current−voltage (I−V) characteristics in combination with the low organic bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…In addition to our direct observations, other researchers’ work also provides evidence that any molecule directly connected to ferromagnetic electrodes undergoes dramatic changes. Recently, experimental studies showed that the hybridization of Cu-phenalenyl molecule and cobalt electrode energy states yields net magnetic moment on the molecules (with 1/2 spin state) near the interface at room temperature 47 . Spinterface, the interface between molecules and the magnetic electrodes, has started taking the form of a sub-branch in spintronics due to a spin-filtering-like phenomenon impacting the molecules and magnetic electrodes simultaneously 48 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to our direct observations, other researchers’ work also provides evidence that any molecule directly connected to ferromagnetic electrodes undergoes dramatic changes. Recently, experimental studies showed that the hybridization of Cu-phenalenyl molecule and cobalt electrode energy states yields net magnetic moment on the molecules (with 1/2 spin state) near the interface at room temperature 47 . Spinterface, the interface between molecules and the magnetic electrodes, has started taking the form of a sub-branch in spintronics due to a spin-filtering-like phenomenon impacting the molecules and magnetic electrodes simultaneously 48 .…”
Section: Methodsmentioning
confidence: 99%
“…Transport properties serve as a crucial tool to understand the scattering mechanisms in the two-dimensional electron gas (2DEG) channel effectively. Various characterization techniques have been employed to ensure the production of high-quality samples. Magnetoresistance measurements in quantum transport serve as a powerful tool for characterizing compound semiconductors, facilitating a deeper understanding of their electronic properties. Quantum oscillations and their scattering phenomena have been extensively explored in various GaN based heterostructures. ,, However, the quantum transport behaviors in this high-mobility InAlN/GaN heterostructure have not been widely reported. In particular, study on the InAlN/GaN 2DEG systems with high mobility remains a long-standing challenge due to growth challenges.…”
Section: Introductionmentioning
confidence: 99%